2013
DOI: 10.1073/pnas.1308453110
|View full text |Cite
|
Sign up to set email alerts
|

The DMAP interaction domain of UDP-GlcNAc:lysosomal enzyme N -acetylglucosamine-1-phosphotransferase is a substrate recognition module

Abstract: UDP-GlcNAc:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (GlcNAc-1-phosphotransferase) is an α 2 β 2 γ 2 heterohexamer that mediates the initial step in the formation of the mannose 6-phosphate recognition signal on lysosomal acid hydrolases. We previously reported that the specificity of the reaction is determined by the ability of the α/β subunits to recognize a conformationdependent protein determinant present on the acid hydrolases. We now present evidence that the DNA methyltransferase-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…With regard to the role of the ␣DMAP interaction domain, it should be noted that we previously reported that the K732N and L785W missense mutations in this domain were defective in phosphorylating purified porcine CathD in vitro, and the K732N mutant was impaired in correcting the phenotypic abnormalities observed in a zebrafish model of ML II (13). Therefore, it was surprising that the ⌬DMAP mutant phosphorylated CathD quite well in the current transfection studies while exhibiting defective phosphorylation of several other lysosomal hydrolases.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…With regard to the role of the ␣DMAP interaction domain, it should be noted that we previously reported that the K732N and L785W missense mutations in this domain were defective in phosphorylating purified porcine CathD in vitro, and the K732N mutant was impaired in correcting the phenotypic abnormalities observed in a zebrafish model of ML II (13). Therefore, it was surprising that the ⌬DMAP mutant phosphorylated CathD quite well in the current transfection studies while exhibiting defective phosphorylation of several other lysosomal hydrolases.…”
Section: Discussionmentioning
confidence: 73%
“…␣-GalA was a generous gift from Amicus Therapeutics (Cranbury, NJ), whereas ␣-iduronidase was kindly provided by William Canfield (Genzyme, Boston, MA). GST and GST fusions were expressed in and purified from Escherichia coli BL21 (RIL) cells (Agilent Technologies), and pulldown assays were performed with the purified lysosomal enzymes exactly as described (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GNPTAB-V5/His in pcDNA6 (kind gift from W. Canfield, Genzyme, Cambridge, MA; see ref. 24) was modified by quick-change sitedirected mutagenesis (Stratagene) to generate K4Q, S15Y, and S399F phosphotransferase αβ subunits. See SI Materials and Methods for the primer sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Confocal immunofluorescence microscopy was performed as described in ref. 24. See the SI Materials and Methods for more details.…”
Section: Methodsmentioning
confidence: 99%